The role of identity in chronic pain cognitions and pain-related disability within a clinical chronic pain population. (January 2022) - Reed, David E; Cobos, Briana; Nagpal, Ameet S; Eckmann, Max; McGeary, Donald D
Objective: Chronic pain has a significant impact on functioning and results in the disruption of one's assumed life trajectory, potentially altering their self-perceived identity. The present research is designed to determine whether identity-related issues are associated with common chronic pain cognitions and pain-related disability, which may help inform understanding of clinical chronic pain populations. Method: Ninety-eight adult chronic pain patients were assessed at a local pain clinic during a regularly scheduled appointment focusing on pain management. Multivariate hierarchal regression was used to determine whether issues related to identity and death anxiety were associated with pain catastrophizing, pain acceptance, and pain-related disability, above and beyond pain severity, fear-avoidance, and age. Results: Self-concept clarity was significantly related to pain catastrophizing and pain acceptance, above and beyond death anxiety, pain severity, fear-avoidance, and age. Death anxiety was associated with pain catastrophizing, pain acceptance, and pain-related disability above and beyond pain severity, fear-avoidance, and age. Conclusions: To the best of our knowledge, the present study is the first examination of self-concept clarity and death anxiety as they relate to pain catastrophizing, pain acceptance, and pain-related disability. These descriptive results support the inclusion of identity and death anxiety within the pain experience and could serve as a foundation for future directions relevant to clinical applications.